Associação entre transtorno do espectro autista e doença periodontal: estudo caso-controle - Silva, Aline Hübner da (2020)
Introduction: Autism Spectrum Disorder (ASD) can affect several body systems, resulting in a variety of demands in health care areas. Objective: To evaluate the association between periodontal diseases and ASD. Methods: In this case-control study, 40 cases with ASD and 40 controls with typical development were selected by convenience in four cities in the North of the state of the Rio Grande do Sul and then matched by gender and age (+/- 2 years). The outcome of periodontal disease was identified after a clinical dental exam. The odds ratio (OR) of the association between ASD and periodontal diseases was calculated. Results: The participants were children and adolescents from 5 to 15 years of age, predominantly male (85%). The presence of gingival bleeding did not differ between cases and controls [47.5% vs. 45% (95%CI: 1,1(0.41-2.92)], as well as for the presence of biofilm/plaque [77.5% vs. 62.5% (95% CI: 2.0 (0.70 -6.28)] and calculus [52.5% vs. 30% (95% CI: 2.5 (0.93-7.18)]. The need for periodontal treatment was similar between groups (p = 0.225), where the supervision of a dental surgeon proved to be fundamental for periodontal health. The performance of oral hygiene done by third parties (p = 0.001) and the abandonment of dental treatment (p=0,021) was significantly higher in the group of participants with ASD. Conclusion: ASD is not associated with periodontal diseases. The administration of oral hygiene by caregivers of participants with ASD proved to be effective when compared with indices of periodontal diseases in their peers with typical development.